Health inequalities - Anne Case; Lucy Kraftman (Institute for Fiscal Studies (IFS), 2022)
There are marked differences in life expectancy between the regions of England, between the countries in the UK, and between the UK and other wealthy countries. Within England, prior to the COVID-19 pandemic, life expectancy at birth was more than two years higher in London and the South East than in the North of England. For decades, life expectancy in Scotland has been two years lower than in other constituent countries. Throughout the UK, gains in life expectancy slowed considerably after 2010, proximately attributable to a slowdown in progress against cardiovascular disease. After many years of gains in life expectancy, something has gone seriously wrong. In 2019, the UK ranked 24th in the OECD in life expectancy, behind all other English-speaking countries (with the exception of the US) and nearly all countries of Western Europe.
Keywords: 330; Health and social care; Poverty; inequality and social mobility; Health; Healthcare; Inequality